Die Typen der von Julius Weise (1844-1925) beschriebenen Staphylinidae-Arten (Coleoptera). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1988)
The collection of the Department of Insect Taxonomy in the Eberswalde branch of the Institute of Plant Protection Research (former Deutsches Entomologisches Institut) includes types of 22 species from 30 Staphylinidae species described by Weise from 1875 to 1879. The types of further 5 species are preserved in the collection of the Museum of Natural History of the Humboldt-Universität Berlin. All types are listed alphabetically. References represent a bibliography to Weise’s taxonomic Staphylinidae papers.